PENGEMBANGAN MODEL KNOWLEDGE SHARING PADA ORGANISASI PEMBELAJAR (LEARNING ORGANIZATION : KAJIAN PADA PERGURUAN TINGGI NEGERI & SWASTA DI PULAU LOMBOK) - Hermanto; Agusdin; Baiq Handayani Rinuastuti (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2022)
This study aims to explain and examine the direct influence of organizational culture and transformational leadership on knowledge sharing among lecturers at universities in West Nusa Tenggara, Indonesia. A quantitative approach in which data is collected based on a survey method. The data analysis technique used in this research is Partial Least Square (PLS). The population of this research is the teaching staff who are involved as a research unit where 200 lecturers are used as research respondents, but only 193 questionnaires that meet the requirements to be used as research data. The results showed that there was a positive and significant direct effect on knowledge sharing and a positive and significant direct influence of culture between transformational leadership on knowledge sharing. The results also show that organizational culture has a positive and significant direct effect on knowledge sharing. This shows that the stronger the organizational culture, the better the implementation of perceived knowledge sharing. In addition, the results of the study show that transformational leadership has a positive and significant effect on knowledge sharing. That is, the more effective the transformational leadership, the better the implementation of knowledge sharing with lecturers at the university. Key Words: transformational leadership. Organizational culture, and knowledge sharing